The Sixth Ukrainian-Polish and Second EastEuropean Meeting on Ferroelectrics Physics (September 6–10, 2002, Uzhgorod-Synjak, Ukraine) (Condensed Matter Physics, 2003)
This issue contains Proceedings of the Sixth Ukrainian-Polish and Second EastEuropean Meeting on Ferroelectrics Physics held in Synjak on September 6–10, 2002. Such joint international conferences devoted to the problems of phase transitions and ferroelectricity have been carried out by Ukrainian and Polish scientists during the last decade.